EFFECTS OF INTERMITTENT HOT WATER TREATMENT ON CHERRY QUALITY - Na Zhang1; Yuxian Ding; Qinggang Wang; Aiqiang Chen (Journal of Animal and Plant Sciences, 2020)
In order to explore the reasons for preservation effect of hot water treatment on cherries, intermittent treatment was introduced to amplify the heat transfer factor. Cherries were immersed in hot water (42℃) for 10 (C1), 15 min (C2) continuously, or for 10 (IN1), 15 (IN2) min intermittently, respectively, and the intermittent treatment was realized through the temperature return process by room temperature water (20 °C) after every 5 min continuous treatment. Results showed that Group IN1, IN2 and C1 performed better than the untreated Group CK, and Group IN1 performed the best. At the fifteenth day, the weight loss ratio, browning index and respiration intensity of Group IN were 83.1%, 62.3% and 71% of that of Group CK, respectively, the soluble solid and titratable acid content of Group IN1 were effectively preserved, and Group IN1 also maintained good hardness, brittleness and cellular microstructure. The poor-quality and severe cell damage indicated that Group C2 had the worst performance and showed irreversible thermal damage. Continuously 15 min soaking in hot water exceeded the safety threshold time of treatment for the cherries, and under the same valid treatment time period, intermittent treatment showed positive performance and avoided irreversible thermal damage.
Keywords: Cherry; Intermittent hot water treatment; Quality; Heat transfer characteristics